A panoramic view of chronic liver diseases and natural remedies reported in Traditional Persian Medicine - M. Zarshenas, Mohammad; Ranjbar Farrokhi, Ratin; Akhavein, Mahshad; Reza Kiafar, Mohammad (Current Pharmaceutical Design, 2016)
Regarding limited effectiveness of many hepatic medical approaches, seeking for novel treatment strategies is crucial to improve outcomes. Hence, the current study aims to compile a concise but critical review over reported liver diseases and related medicinal plants from the Persian medicine perspectives. To this end, five main pharmaceutical manuscripts of Persian medicine from 9th-18th A.D. as well as the latest and largest medical textbook of Persian medicine were studied. By searching through databases such as PubMed and ScienceDirect, mechanisms or pharmacological activities of reported medicinal plants in the field of liver diseases were cited and discussed. In all, seventeen different liver diseases, mainly chronic, were cited in Persian medicine. Ninety three medicinal plants with liver tonic, hepatoprotective and related effectiveness belonging to 49 families were derived and authenticated from these studied manuscripts. More than 75% of the herbs showed related hepatoprotectivity and antioxidant activities. However, none of them have been examined clinically. Besides historical clarification, the current investigation compiled an evidence- based study on reported liver herbal remedies from the standpoints of Persian scholars. Conducting attributable clinical trials against the backdrops of proven in vitro and in vivo studies may result in new treatment discoveries for liver diseases.
Keywords: literature research